Protection of Notaries as Controllers and Processors of Personal Data of Litigants - Hartanto, Stefanie; Putri, Prisilia Permata (Jurnal Ius Constituendum, 2025)
This research examines the prevention and protection measures that can be taken by notaries in their dual role as controllers and processors of personal data. This research is motivated by the limited awareness of some notaries regarding their legal obligations to protect the personal data of witnesses, as mandated by the Personal Data Protection Law (UUPDP). This research contributes new insights by framing notaries as Controllers and Processors under the UUPDP, an aspect that has rarely been emphasized in previous legal literature. The novelty of this study lies in its specific focus on notaries’ dual capacity as both Controllers and Processors of personal data under Indonesian law, particularly in the context of witness data handling an area that has not been thoroughly examined in existing scholarship. Using normative juridical methods with statutory and conceptual approaches, this study found that notaries have dual responsibilities in managing witness data and must proactively comply with the UUPDP to prevent legal risks. These responsibilities include obtaining approvals, establishing internal data protection policies, and implementing secure technologies such as encryption and regular audits. Strengthening the role of notaries in personal data protection will foster greater legal certainty and public trust in the notary profession. The integration of these findings with practical recommendations emphasizes the need for regulatory guidance and professional capacity building to support compliance with personal data protection standards.